2011
DOI: 10.1007/s00216-011-5287-6
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate classification of pigments and inks using combined Raman spectroscopy and LIBS

Abstract: The authenticity of objects and artifacts is often the focus of forensic analytic chemistry. In document fraud cases, the most important objective is to determine the origin of a particular ink. Here, we introduce a new approach which utilizes the combination of two analytical methods, namely Raman spectroscopy and laser-induced breakdown spectroscopy (LIBS). The methods provide complementary information on both molecular and elemental composition of samples. The potential of this hyphenation of spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 30 publications
1
64
0
1
Order By: Relevance
“…As already stated, applied jointly, the two techniques present a cooperative analytical advantage, with elemental composition information obtained via LIBS analysis complementing the molecular information provided by Raman spectroscopy, thus leading to an integrated characterization of pigments and minerals, superior to those obtained with the individual Raman or LIBS data sets alone [21][22][23][24]. Particularly, in the context of wall painting analysis, research studies by Bruder et al [25] illustrate the complementarity of LIBS and Raman microscopy for the in situ analysis of fresco replicas while Westlake et al [26] have demonstrated the combined use of the techniques in the analysis of mural painting fragments, still performing analyses on small plaster fragments in the analytical laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…As already stated, applied jointly, the two techniques present a cooperative analytical advantage, with elemental composition information obtained via LIBS analysis complementing the molecular information provided by Raman spectroscopy, thus leading to an integrated characterization of pigments and minerals, superior to those obtained with the individual Raman or LIBS data sets alone [21][22][23][24]. Particularly, in the context of wall painting analysis, research studies by Bruder et al [25] illustrate the complementarity of LIBS and Raman microscopy for the in situ analysis of fresco replicas while Westlake et al [26] have demonstrated the combined use of the techniques in the analysis of mural painting fragments, still performing analyses on small plaster fragments in the analytical laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…However, such methods are invasive and time-consuming [6], and these disadvantages must be considered. Different approaches, such as Raman spectroscopy [7][8][9][10], UV-Vis spectroscopy [4,11], and IR spectroscopy [12], are based on the interaction of light with the substrate. Those methods ensure the physical integrity of the document, and yield data on organic and inorganic components of a sample.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has become important in recent years due to its variety of applications in areas such as mineralogy, forensics, biology and medicine [5][6][7][8][9]. It is currently used for the characterizat ion of drugs, bone structures, organic pesticides, among others [10][11][12].…”
Section: Introductionmentioning
confidence: 99%